The incidence rate of female breast cancer in Saudi Arabia: an observational descriptive epidemiological analysis of data from Saudi Cancer Registry 2001–2008 - Alghamdi IG (Dove Medical Press, 2013)
Ibrahim G Alghamdi,1 Issam I Hussain,1 Mohamed S Alghamdi,2 Mohamed A El-Sheemy1,3 1University of Lincoln, Brayford Pool, Lincoln, United Kingdom; 2Ministry of Health, General Directorate of Health Affairs Al-Baha, Kingdom of Saudi Arabia; 3Lincoln Hospital, Research and Development, United Lincolnshire Hospitals, National Health Service Trust, Lincoln, United Kingdom Background: This study presents descriptive epidemiological data related to breast cancer cases diagnosed from 2001 to 2008 among Saudi women, including the frequency and percentage of cases, the crude incidence rate (CIR), and the age-standardized incidence rate (ASIR), adjusted by the region and year of diagnosis. Methods: This is a retrospective descriptive epidemiological study of all Saudi female breast cancer cases from 2001 to 2008. The statistical analyses were conducted using descriptive statistics, a linear regression model, and analysis of variance with the Statistical Package for the Social Sciences version 20 (IBM Corporation, Armonk, NY, USA). Results: A total of 6,922 female breast cancer cases were recorded in the Saudi Cancer Registry from 2001 to 2008. The highest overall percentages (38.6% and 31.2%) of female breast cancer cases were documented in women who were 30–44 and 45–59 years of age, respectively. The eastern region of Saudi Arabia had the highest overall ASIR, at 26.6 per 100,000 women, followed by Riyadh at 20.5 and Makkah at 19.4. Jazan, Baha, and Asir had the lowest average ASIRs, at 4.8, 6.1, and 7.3 per 100,000 women, respectively. The region of Jouf (24.2%; CIR 11.2, ASIR 17.2) had the highest changes in CIR and ASIR from 2001 to 2008. While Qassim, Jazan and Tabuk recorded down-trending rates with negative values. Conclusion: There was a significant increase in the CIRs and ASIRs for female breast cancer between 2001 and 2008. The majority of breast cancer cases occurred among younger women. The region of Jouf had the greatest significant differences of CIR and ASIR during 2001 to 2008. Jazan, Baha, and Najran had the lowest average CIRs and ASIRs of female breast cancer, whereas the linear trend upward is a concern in certain regions, such as the eastern region, Makkah, and Riyadh. However, further analytical epidemiological research is needed to identify the potential risk factors involved in the increase in the prevalence of breast cancer among Saudi women. Keywords: epidemiology, breast cancer, morbidity measure, public health, cancer epidemiology